School and Non-Governmental Organizations Partnership in Benefit of the Local Community - Camelia STĂICULESCU; Maria Liana LACATUŞ (Revista de Management Comparat International)
School is a complex social institution with specific role in a community. Each school works together with other institutions and organizations in a specific environment with characteristics that may differ from a community to another. Schools have developed many forms of partnership with NGOs in order to achieve different educational objectives. Such forms of partnership have positive impact and benefits for students and their families, teachers, and community as well. This is why entities involved in educational partnerships have to act responsible and to build their actions primarily based on students’ needs and interests. The present paper analyses the complexity of circumstances in which the partnerships between schools and NGOs works and also forms of partnership and the interdependence between schools and NGOs from the perspective of partnership’s consequences. Some recommendations are presented to improve the partnership between schools and NGOs management and increase the level of social responsibility of involved actors and entities.